Numerical prediction of the effects of longitudinal crack-like laminations on the tensile properties of wires - Adewole, Kazeem K. (Journal of Civil Engineering and Management, 2016)
Carbon steel wires used for civil engineering applications may contain laminations. In the published literature, lamination was modelled as a separation between two faces with a finite distance. This technique is not suitable for modelling the line-type/crack-like laminations that may be present in the wires. In this paper, the effects of longitudinal line-type laminations on the tensile properties of carbon steel wires were investigated using Finite element (FE) analysis. Laminations were modelled as seams which truly simulate the line-type/crack-like laminations that have been reported to be instrumental to the failure of pre-stressing wires. FE analysis revealed that laminations do not significantly reduce the yield and ultimate loads of the wires. However, laminations cause a significant reduction in the displacement at fracture of the wires and the reduction is proportional to the length of the laminations. Consequently, the presence of laminations reduces the ductility of the wires, which reduces the ability of the wires to withstand overload the wires may experience in service without causing a catastrophic failure of structures where wires provide the required reinforcement.